In deriving the unbiasedness of OLS Estimators,

$$\hat{\beta_1} = \beta_1 + \frac {\sum_{i=1}^{n} (x_i - \bar{x})u_i}{\sum_{i=1}^n (x_i - \bar{x})^2}$$

My professor changes the above to:

$$\hat{\beta_1} = \beta_1 + \sum_{i=1}^{n} (\frac {(x_i - \bar{x})}{\sum_{i=1}^n (x_i - \bar{x})^2})u_i$$

How are these two equal?

  • $\begingroup$ This is an expression of the distributive law (of multiplication over addition). $\endgroup$
    – whuber
    Apr 24, 2023 at 13:10

1 Answer 1


Note: The denominator $ \sum_{i=1}^n (x_i - \bar{x})^2 := s$ is constant; it doesn't change when you are summing over $i,$ i.e. the summation would be $\sum_i \left(\frac{(x_i-\bar x)}{s}\right)u_i.$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.